2014
DOI: 10.1051/0004-6361/201118484
|View full text |Cite
|
Sign up to set email alerts
|

Optical and infrared observations of the young SMC blob N26 and its environment

Abstract: Context. High-excitation compact H  regions of the Magellanic Clouds are sites of recent massive star formation in low metallicity environments. Aims. Detailed study of these regions and their environments using high-spatial resolution observations is necessary to better understand massive star formation, which is still an unsolved problem. We aim at a detailed study of the Small Magellanic Cloud compact H  region N26, which is only ∼4 in diameter.Methods. This study is based on high spatial resolution ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
6
0
1
Order By: Relevance
“…Beam dilution decreases this even further to N C ≤ 5 × 10 15 cm −2 . For the source complex N 25+N 26 the numbers are less clear, but we estimate in a similar way from the radio flux (Filipović et al 2002) and the electron densities (≈10 3 cm −3 - Testor et al 2014) an emission measure E.M. = 7 × 10 4 pc cm −6 and column densities N H = 2 × 10 20 cm −2 , from which we find N C ≤ 2 × 10 15 cm −2 once again after taking beam dilution into account. In either case, the contribution of the H II region to the (ionized) carbon column density is not more than 2−5 per cent.…”
Section: Ionized Carbon In [Hii] Regionsmentioning
confidence: 54%
See 1 more Smart Citation
“…Beam dilution decreases this even further to N C ≤ 5 × 10 15 cm −2 . For the source complex N 25+N 26 the numbers are less clear, but we estimate in a similar way from the radio flux (Filipović et al 2002) and the electron densities (≈10 3 cm −3 - Testor et al 2014) an emission measure E.M. = 7 × 10 4 pc cm −6 and column densities N H = 2 × 10 20 cm −2 , from which we find N C ≤ 2 × 10 15 cm −2 once again after taking beam dilution into account. In either case, the contribution of the H II region to the (ionized) carbon column density is not more than 2−5 per cent.…”
Section: Ionized Carbon In [Hii] Regionsmentioning
confidence: 54%
“…N 25 is one of a group of H II regions also containing the compact N 26, the large and diffuse N 22, and N 21 and N 23 (Testor 2001;Testor et al 2014) in the crowded southwestern SMC Bar. The ionization of each of the nebulae appears to be dominated by a single O star.…”
Section: Introductionmentioning
confidence: 99%
“…Embedded young massive stars can manifest themselves as YSOs or (ultra-)compact H II regions (see, e.g., Heydari-Malayeri et al 2002;Testor et al 2014, for examples of the latter). Both are known to be quite numerous in the SMC.…”
Section: Embedding In Birth Cloudsmentioning
confidence: 99%
“…Kamath et al (2014) identified 63 stellar sources in the SMC that appear to be intermediate-mass YSOs, of which 27 exhibit optical line emission, and 23 exhibit strong UV excesses. Testor et al (2014) identified 12 massive YSO candidates in the H II region N26 in the SMC using infrared and optical imaging and spectroscopy. Ruffle et al (2015) introduced a systematic method for classifying mid-infrared (MIR) point sources in the SMC, identifying 10 sources as candidate HAeBe stars (YSO-4 in their classification system) and Ward et al (2017) recently obtained NIR spectra of 17 massive YSOs in the SMC identifying extended molecular hydrogen and Brγ emission, enabling a comparison of SMC and Galactic YSOs.…”
Section: Introductionmentioning
confidence: 99%